Effect of Zinc Oxide Nanoparticles in Drinking Water on Growth Rate, Biochemical Parameters, and Intestinal Histology of Broilers - Arkan B. Mohammed; Oday K. Hamad; Thamer A. Khttab (Advances in Agriculture)
The study objectives were to evaluate effects of zinc oxide nanoparticles (ZnO NPs) on growth rate, gut histomorphology, and physiological parameters of broilers. A total 360 birds were randomly assigned into five groups (n = 72 birds per group; four replicates per group n = 18), the control group drink water without nano zinc, and ZnO NP groups added 6, 8, 10, and 12 mg/liter to drinking water. The results presented that ZnO NP groups showed significant (p<0.05) in growth performance with reduced feed intake in all ZnO NP groups in comparison to the control at 35 and 42 days of age. Villus height and villi to crypt ratio showed significant differences (p<0.05) in all ZnO NP groups compared to the basal control, but the results showed there was no significant difference (p<0.05) between the ZnO NP and control in crypt depth. There was no significant effect of ZnO NP on total protein and albumin in broiler serum compared to the control at 35 and 42 days of age. The data showed that ZnO NP had a positive effect and improved the ratio of serum globulin and globulin to albumin compared to the others of broilers at 35 and 42 days of age. On the other hand, liver enzyme activity was significantly (p<0.05) different in ZnO NP groups compared to the basal control. The inclusion of ZnO NPs in drinking water significantly improved growth performance and gut histomorphology, and it had an impact on antioxidant and biochemical parameters.